Economic Clusters, Knowledge Networks and Globalization: Fruit Growing in Dutch Limburg, 1850-1940 - Segers, Yves (TSEG - The Low Countries Journal of Social and Economic History, 2016)
This paper unravels and analyses how the fruit sector in the province of Limburg (The Netherlands) reacted to growing (inter)national competition between 1850 and 1940. Entrepreneurs, private and public organisations created shared facilities which operated on a regional scale, such as auctions and a state horticultural consultancy, to respond to this global competition and to stimulate the formation of a regional fruit cluster. This process of economic development is embedded in the emergence of knowledge networks, in which scientific and economic know how, mainly regarding product and processing quality, circulated between various actors. Initially, the fruit cluster operated mainly in a regional network, but from the First World War onwards it became increasingly integrated in a national network, steered by the government and agricultural associations.